Thermal load of buildings as a parameter of energy efficiency of the heating system - Kolienko, A.; Shelimanova, O. (Energy and Automation, 2025)
Reducing heat energy consumption and increasing energy efficiency at all stages of heat transformation in district heating systems is a key measure to combat climate change, which is the goal of the EU energy policy. The value of the calculated heat load (CHL) is the basis for determining the heat carrier consumption in the heat networks of district heating systems. However, the inconsistency of regulatory documentation and changes taking place in the field of heat supply have led to the fact that today there is no generally accepted methodology for determining this value. The purpose of the study is to compare existing methods for determining the value of CHL for heating needs and to provide recommendations for the correct determination of this indicator for different categories of buildings. The general principles of calculating the heat load for heating and ventilation systems of residential and public buildings are considered. Problems that arise during the determination of the value of the connected heat load for district heating systems are noted. Recommendations are given on ways to solve such problems/ Key words: connected heat load, calculated heat losses, thermal resistance, heating and ventilation